Potential of Bay Leaf as Tablet Fumigant against Cadra cautella (Walker) (Lepidoptera: Pyralidae) - Nino Trifatu Ramadhan; Ludji Pantja Astuti; Bambang Tri Rahardjo (Agrotechnology Research Journal, 2025)
Bay leaf contain active ingredients that have potential as a botanical fumigant against stored product pests. Using bay leaves as tablet fumigant has been limited to controlling stored product pests from the order Coleoptera. It has not been used to control stored product pests from the order Lepidoptera. Therefore, this research aimed to determine the effect of bay leaf tablet fumigants on the developmental stages of C. cautella. This research consisted of six different concentration levels (i.e., 0; 1; 2; 3; 4; and 5 ml l-1 air) repeated five times and arranged with a Completely Randomized Design (CRD). The observed variables were the mortality on the developmental stages of C. cautella. The results showed that mortality of eggs, larvae, and adults of C. cautella was higher (100%) at 3, 4, and 5 ml l-1 air than other concentrations. The LC50 values on eggs, larvae, and adults of C. cautella were (0.956, 0.982, 1.221 ml l-1 air at 24 hours), (0.912, 0.952, 0.895 ml l-1 air at 48 hours), and (0.502, 0.938, 0.880 ml l-1 air at 72 hours), respectively.